Interactive education with exploration of virtual reality technology in Mathematic subject / Siti Hazyanti Mohd Hashim - Mohd Hashim, Siti Hazyanti (2023)
Nowadays, technology plays a fundamental role in the development of daily life activities. In this regard, there is an increase in disciplines that have used technologies, with educational fields standing out above all. Within education, there are a series of emerging technologies that are increasingly implemented in the classroom. The use of virtual reality in education is a good way to attract them to learn. Using virtual reality in learning has a positive impact on the trend of increasing motivation, more attraction, and fast learning.